Symbolic Psycho-Sufism of Sunan Kalijaga in Serat Dewa Ruci: A Semiotic Analysis of Ferdinand de Saussure - Agung Drajat Sucipto (Journal of Indonesian Islamic Studies, 2026)
Serat Dewa Ruci is one of the most significant works of Javanese Islamic literature, containing symbolic narratives that reflect the integration of local wisdom and Sufi teachings within the tradition of cultural da‘wah associated with Sunan Kalijaga. While previous studies have primarily examined the text from philosophical, cultural, and mystical perspectives, limited attention has been given to its symbolic structure as a system of psycho-sufistic meanings. This study aims to analyze the symbolic elements embedded in Serat Dewa Ruci using Ferdinand de Saussure’s semiotic theory and to interpret their meanings through a psycho-sufistic framework. Employing a qualitative library research design, the study examines symbolic episodes, characters, and narrative elements found in the text, focusing on the relationships between signifiers and signified meanings. The findings reveal six major symbols that structure Bima’s spiritual journey: Mount Candramuka, the Tribaksara Forest, Rukmuka and Rukmakala, the Dragon, the Ocean and tirta pawitra sari, and Dewa Ruci. Semiotic analysis demonstrates that these symbols form an interconnected system of meanings representing successive stages of spiritual development. Through a psycho-sufistic interpretation, the symbols are found to signify the strengthening of faith, awareness of human vulnerability, responsibility for worldly blessings, emotional regulation, the search for ultimate truth, and the attainment of divine self-knowledge. The study contributes to Islamic studies by demonstrating how symbolic narratives function as vehicles for transmitting spiritual teachings within Javanese Islamic culture. Furthermore, it offers a novel integration of Saussurean semiotics and psycho-sufistic analysis, providing a new perspective on the relationship between literature, spirituality, and cultural da‘wah in the intellectual legacy associated with Sunan Kalijaga.